Nematodes Follow a Leader - Erdogan, Hilal; Cruzado-Gutierrez, Karin; Stevens, Glen; Shapiro-Ilan, David; Kaplan, Fatma; Alborn, Hans; Lewis, Edwin (Frontiers in Ecology and Evolution, 2021)
Aggregated movement and population structure are known in entomopathogenic nematodes, which are obligate insect parasites. Aggregation behavior in the absence of external stimuli suggests communication among individuals, often in the form of trail-following, which has not been shown by nematodes of any kind. Interactions among individuals are an essential basis of following behaviors and can have significant fitness consequences. We explored intraspecific and interspecific interactions among three Steinernema species (S. glaseri, S. carpocapsae, and S. feltiae) in terms of trail following, and fitness outcomes of following heterospecific individuals. We found that the following behavior is context dependent. Following behavior among conspecifics was significantly increased when the lead nematode had prior contact with host cuticle. However, we did not find a clear association between the following response to heterospecific IJs and their reproductive success in a co-infected host.